Hierarchical superstructures from a star-shaped molecule consisting of a cyclic oligosiloxane with cyanobiphenyl moieties. Issue 1 (14th November 2014) - Kim, Dae-Yoon; Park, Minwook; Lee, Sang-A; Kim, Soeun; Hsu, Chih-Hao; Kim, Namil; Kuo, Shiao-Wei; Yoon, Tae-Ho; Jeong, Kwang-Un
Abstract : A star-shaped molecule synthesized by connecting four cyanobiphenyl mesogens to the periphery of a super-hydrophobic and ultra-flexible cyclic siloxane ring with hexyl chains formed hierarchical layered superstructures. Abstract : Unconventional star-shaped liquid crystals (abbreviated as SiLCs) were successfully synthesized by chemically connecting four cyanobiphenyl anisotropic mesogens to the periphery of a super-hydrophobic and ultra-flexible cyclic tetramethyltetrasiloxane ring with flexible hexyl chains. Based on the combined experimental techniques of differential scanning calorimetry (DSC), cross-polarized optical microscopy (POM), solid-state carbon-13 ( 13 C) nuclear magnetic resonance (NMR) spectroscopy and one-dimensional (1D) wide-angle X-ray diffraction (WAXD), it was found that the SiLC molecule exhibited the monotropic phase transition from a LC phase to a crystalline phase. The crystalline phase was only detected during slow heating processes above its glass transition temperature, while a LC phase was formed both during cooling and during heating processes. The hierarchical superstructures were identified from the structure-sensitive 2D WAXD of the macroscopically oriented SiLC film and confirmed by selected area electron diffraction (SAED) of the SiLC single crystals. The molecular packing symmetry in the monoclinic unit cell was further investigated by computer simulations on the real and reciprocal spaces. Macroscopically oriented SiLC hierarchical superstructures on the different length scales may provide the targeted physical properties, which can allow us to apply SiLC molecules in the fields of electro-optical devices and nonlinear optics.